IMPLEMENTASI TEKNOLOGI PENGELOLAAN TANAMAN TERPADU DAN DAMPAKNYA TERHADAP PENDAPATAN PETANI JAGUNG (Zea mays L.) HIBRIDA - Syamsiah, Milla; Marina, Ida; Dinar, Dinar (Journal of Sustainable Agribusiness, 2025)
The purpose of this study was to determine the level of application of integrated crop management technology and its impact on the income of hybrid corn farmers, the amount of income of hybrid corn farmers who use PTT and Non-PTT technology. This study was conducted in Babakanjawa Village, Majalengka District, Majalengka Regency. The method used in this study was a survey method that was limited to sample farmers who participated in the Integrated Crop Management (PTT) system approach model as many as 30 people and non-PTT model participants as many as 18 people. The analysis used was to calculate the income of PTT and non-PTT corn farming per hectare, cash costs of PTT and non-PTT corn farming, costs calculated for PTT and non-PTT corn farming, and income from PTT and non-PTT corn farming. The results of the study can be concluded that there are differences in productivity due to technology, as well as differences in quality that cause differences in price, where the income from total costs for PTT farmers is IDR 6.247.824,00, while non-PTT farmers are only IDR 2.475.494,00.